A review on the relationship between the fish length and otolith biometry - Taştan, Yiğit; Sönmez, Adem Yavuz (Prensip Publishing, 2021)
In teleosts, biometric parameters of certain bony structures are used for the age and/or size determination of the fish. Otolith is perhaps the most widely used of these bony structures. There are numerous studies which have shown that otolith biometry is positively and strongly correlated with fish size. In this paper, some recent studies that investigate the relationship between otolith biometry and fish length are summarized. It is possible to estimate fish size and/or age by knowing this relationship. This information can be useful, especially when it is not possible to sample a certain portion of a fish population. Besides, otoliths found in archaeological excavation sites or in the stomachs of predators can provide information about the fish they belong to. These data are useful to taxonomists, paleobiologists, and researchers studying the nutritional biology of predators.
Keywords: 14. Life underwater